PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 16 BANDAR JAYA - Siti Maryani; Eddy Noviana; Syahrilfuddin Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study was motivated by the low learning outcomes IPA fourth grade students of SD Negeri 16 Bandar Jaya, totaling 16 students with KKM 70 just 6 students, or 37.5% of the children who completed while 10 students or 62.5% were completed. According to this problem, the researchers have conducted research using Action Research (PTK) by applying Cooperative Learning Model two stay two stray. In the first cycle of the first meeting of teachers percentage activity obtained at 58, 33% with enough categories, the second meeting increased to 70.83% in both categories. At the first meeting back in the second cycle increased to 79.16% in both categories, at the second meeting an increase of 91.66% with a very good category. Increased activity of students in cycle 1 the first meeting of the percentage obtained 29.16% are in the category of less, at the second meeting increased to 58.33% with the category enough. Likewise, in the third meeting of the second cycle increased to 62.50% in both categories, the fourth meeting amounted to 83.33% of the increase occurred in the category of being very good. Data learning outcomes of students has increased from the initial data, UH 1, UH II. From the initial data increasing at UH first 65 to 69.0 in the second cycle increased to 80 with an increase of 15.94%. Classical completeness in cycle 1 was 63%. In the second cycle increased to 94% implementation are cooperative learning model two stay two stray can improve learning outcomes IPA fourth grade students of SD Negeri 16 Bandar Jaya.Keywords: Cooperative Model type of two stay two stray, IPA Learning Outcomes